Strategi Marketing Mix dalam Pengembangan Usaha Berdasarkan Analisis Product Life Cycle (PLC): Studi pada Usaha Maharaja Garment Bangkalan - Ema Oktavia Rahmawati; Ety Dwi Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Every business has a goal to achieve profitability and when the business is successful, further development becomes a necessity. Today, the business that continues to grow and is always sought after by people is the convection business. This convection business aims to meet the needs of clothing as people's main clothing by placing orders in large quantities and following the development of trends. An example is the "Maharaja Garment" Convection in Bangkalan, which operates in the midst of competition from similar competitors, so it requires long-term business development to continue to grow. In this context, this research is descriptive, using data collection techniques through observation and documentation. The types and sources of data used include primary and secondary data. This study aims to determine the company's business strategy by applying the Product Life Cycle method. The results of the calculation using the Polli and Cook method show that the convection business of "Maharaja Garment" is in the growth stage. Therefore, the business development is carried out by designing marketing strategies in accordance with the stages of the product life cycle. This strategy includes various product models with superior raw materials, providing guarantees and excellent service, offering discounts, implementing promotions through advertising, and expanding strategic new business premises in the city centre.